2016
DOI: 10.11113/jt.v78.8636
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Gamma Irradiated Fourth Generation Mutant of Rodent Tuber (Typhonium Flagelliforme Lodd.) Based on Morphology and Rapd Markers

Abstract: Rodent tuber (Typhonium flagelliforme Lodd.) is an herbal medicinal plant with anticancer activity. The genetic diversity of rodent tuber is low due to vegetative propagation. Somatic cell population of rodent tuber from Bogor had been irradiated with gamma ray to increase genetic diversity. There were 37 clones of first generation putative mutant (MV1) which had been analyzed based on morphological and RAPD markers. Out of those 37 MV1 clones, there were 17 clones which had undergone genetic mutation and had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 36 publications
0
9
0
1
Order By: Relevance
“…The rodent tuber mutant plants have conducted research through in vitro biotechnology (somaclonal combination) with gamma ray irradiation to produce mutant plants. The results showed that the mutant plants have characteristics morphology changes in the number of leaves, plants height, and wide leaves [5]. The effect of gamma irradiation can also cause genetic changes or mutations.…”
Section: Introductionmentioning
confidence: 99%
“…The rodent tuber mutant plants have conducted research through in vitro biotechnology (somaclonal combination) with gamma ray irradiation to produce mutant plants. The results showed that the mutant plants have characteristics morphology changes in the number of leaves, plants height, and wide leaves [5]. The effect of gamma irradiation can also cause genetic changes or mutations.…”
Section: Introductionmentioning
confidence: 99%
“…Gamma rays successfully irradiated T. flagelliforme plants through combined mutagenesis of somaclonal variations in vitro to increase the number of bioactive compounds contained therein. T. flagelliforme mutant plants have been detected to undergo genetic changes in the first generation (MV1) [5]. The second-generation (MV2) and third-generation (MV3) T. flagelliforme mutants have shown genetic changes through molecular RAPD by comparing wild-type [6].…”
Section: Introductionmentioning
confidence: 99%
“…T. flagelliforme mutant plants have been detected to undergo genetic changes in the first generation (MV1) [5]. The second-generation (MV2) and third-generation (MV3) T. flagelliforme mutants have shown genetic changes through molecular RAPD by comparing wild-type [6]. T. flagelliforme mutant plant received Plant Variety Protection by the Indonesian Ministry of Agriculture in 2020.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro mutagenesis was carried out using a combination of gamma-ray irradiation and somaclonal variation to increase the bioactive compounds in rodent tuber plants. The rodent tuber mutant plants have morphology changes [7], genetic changes [8,9], and protein expression changes [10]. Morphological, genetic, and protein expression changes can reinforce the bioactive compounds in mutant plants.…”
Section: Introductionmentioning
confidence: 99%